Analysis of Students’ Critical Thinking Skills Based on Mathematical Resilience - Pratiwi, Mayasari Dian; Masrukan, Masrukan; Kurniasih, Ary Woro (FKIP Universitas Muhammadiyah Tangerang, 2025)
The purpose of this study was to determine students' critical thinking skills in terms of mathematical resilience. This study used a qualitative research design with a descriptive method. The research was conducted at SMPIT Nurul Islam Tengaran, Semarang Regency, Central Java, during the 2024/2025 academic year. The research subjects were 29 eighth-grade students. The data collection techniques used were a mathematical resilience questionnaire, a critical thinking test, and interviews. The questionnaire was used to determine the category of mathematical resilience. A written essay test was used to assess students' critical thinking skills. Interviews were conducted based on high, moderate, and low mathematical resilience categories. Two students with dominant critical thinking skills were selected from each category. There were two students in the high mathematical resilience category, two in the moderate category, and two in the low category. The results of the questionnaire, written test, and interviews revealed that (1) students in the high and moderate mathematical resilience categories possessed five critical thinking skills, namely interpretation, analysis, inference, evaluation, and explanation, which were both good and complete; (2) students in the low mathematical resilience category only possessed two critical thinking skills, namely interpretation and analysis, which were both good and complete. Based on the research findings, mathematical resilience was found to have an influence on critical thinking skills.